2020
DOI: 10.21608/zjar.2020.94496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Egyptian Propolis on the Bioactive Compounds Content in Tomato Plants

Abstract: Propolis is an organic substance that considered a biostimulant agent and plays a vital role in increasing bioactive compounds content in plants. The study investigated the properties of two different kinds of propolis i.e., Egyptian and Chinese propolis. The physical and chemical analyses results of the Egyptian propolis showed that it contain 253.703 mgGAE/g total phenolic compound, 76.766 mgQE/g total flavonoid compound and 5.417 g/100g total alkaloid. Also, the effect of five concentrations of aqueous extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Compared to the Chinese propolis powder, the Egyptian propolis powder had significantly ( p > 0.05) higher levels of protein, fiber, and antioxidants (total phenolics, total flavonoids, and DPPH), in addition to having a non-aromatic smell. These results are consistent with those reported in other studies [ 15 , 26 ], which found that Egyptian and Chinese propolis have differences in odor and color. This could be due to the geographical differences between Chinese and Egyptian propolis, since the origin of propolis affects the color of the substance.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Compared to the Chinese propolis powder, the Egyptian propolis powder had significantly ( p > 0.05) higher levels of protein, fiber, and antioxidants (total phenolics, total flavonoids, and DPPH), in addition to having a non-aromatic smell. These results are consistent with those reported in other studies [ 15 , 26 ], which found that Egyptian and Chinese propolis have differences in odor and color. This could be due to the geographical differences between Chinese and Egyptian propolis, since the origin of propolis affects the color of the substance.…”
Section: Resultssupporting
confidence: 93%
“…This could be due to the geographical differences between Chinese and Egyptian propolis, since the origin of propolis affects the color of the substance. In addition, the Egyptian propolis was previously reported as significantly higher in fiber, protein, flavonoids, total phenolics, and DPPH contents than Chinese propolis [ 26 ]. These results confirm the health benefits of Egyptian propolis compared to Chinese propolis, and its addition could be a better choice in food processing.…”
Section: Resultsmentioning
confidence: 99%